2005
DOI: 10.1073/pnas.0502383102
|View full text |Cite
|
Sign up to set email alerts
|

Brain and muscle Arnt-like protein-1 (BMAL1), a component of the molecular clock, regulates adipogenesis

Abstract: Brain and muscle Arnt-like protein-1 (BMAL1; also known as MOP3 or Arnt3) is a transcription factor known to regulate circadian rhythm. Here, we established its involvement in the control of adipogenesis and lipid metabolism activity in mature adipocytes. During adipose differentiation in 3T3-L1 cells, the level of BMAL1 mRNA began to increase 4 days after induction and was highly expressed in differentiated cells. In white adipose tissues isolated from C57BL͞6J mice, BMAL1 was predominantly expressed in a fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
344
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(368 citation statements)
references
References 41 publications
(44 reference statements)
13
344
1
5
Order By: Relevance
“…The first direct evidence that adipocytes posses the molecular machinery for a biological clock came from analysis in mice. 20 In 2005, Ando et al 14 demonstrated that the intracellular clock gene system acts in visceral AT and can be influenced by obesity or type 2 diabetes. Recently, it has been documented that these clock genes are expressed in AT from big mammals, specifically horse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first direct evidence that adipocytes posses the molecular machinery for a biological clock came from analysis in mice. 20 In 2005, Ando et al 14 demonstrated that the intracellular clock gene system acts in visceral AT and can be influenced by obesity or type 2 diabetes. Recently, it has been documented that these clock genes are expressed in AT from big mammals, specifically horse.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of BMAL1 in murine 3T3-L1 adipocytes not only induced the expression of several lipid metabolism-related factors, promoting lipogenesis, but also luciferase activity driven by the promoter of Per2, which is a known target gene of BMAL1, was increased. 20,31 A failure in the relationship between both clock genes, highly implicated in adipogenesis, could be influencing body fat distribution and the physiological disturbances related to abdominal fat accumulation. In the present moment, an increasing number of evidences point out that the disruption of the circadian system may have profound clinical relevance in some pathologies, including cancer disease and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bmal1 gene, down-regulated in HF, is a transcription factor playing a central role in the regulation of circadian rhythms and seems to contribute to the regulation of adipogenesis and adipocyte functions (Shimba et al 2005). The Nr1d2 gene, up-regulated in HF, is highly expressed during daylight and represses Bmal1 transcription (Guillaumond et al 2005).…”
Section: Gene Expressionmentioning
confidence: 99%
“…Together, this core circadian regulatory complex constitutes a self-contained feedback loop whose rate-limiting protein levels oscillate in a ∼24-h manner. It is noteworthy that BMAL1, nocturnin, and Rev-erb α have all been implicated as transcriptional regulators of adipogenesis in pre-adipocyte cell models (Shimba et al 2004(Shimba et al , 2005Kawai et al 2010;Kumar et al 2010).…”
Section: Introductionmentioning
confidence: 99%